A Study of the Significance of Translation Studies in the Educational Institutions of Pakistan - Aroob, Faiza (Journal of Communication and Cultural Trends, 2020)
The aim of this research is to highlight the importance of Translation Studies as a proper discipline in educational institutions of Pakistan. The analysis has been done by conducting a questionnaire survey, gathering responses from the students of acknowledged educational institutions, both public and private. The findings suggest rather mixed views of the students about Translation and Translation Studies in general. While most of the participants have a clear idea that translation is something beyond mere paragraph translation and reading translated literature, they view translation as not necessarily a part of Humanities students’ curriculum. Most of the participants have never found an opportunity to take a translation related course; whereas, they are interested in taking one. However, there were only one to two students who could name an institution that offers a translation studies degree. The majority of the students are also aware of the translational processes around them while using social media or reading print media and are able to identify them. On the whole, this research tries to identify the current situation of translation studies in Pakistan, and at the end some recommendations have been given to improve the situation of Translation Studies in Pakistan because Translation Studies is the ultimate requirement for the progress and development in the field of academics. The world has understood this; Pakistan needs to do the same.